(untitled) (Research, Society and Development, 2021)
The intercropping of corn with Urochloa ruziziensis has been widely used for straw formation and weed suppression. In this work, the objective was to evaluate the effects of U. ruziziensis sowing density in intercropping with corn treated or not with glyphosate subdose as well as the performance of cowpea crop grown in succession. The design used was randomized blocks, with four replications. In an intercropping between corn and forage, the factorial scheme 2x3 + 1 was adopted, the first factor being the application or not of the herbicide glyphosate (55 g ha-1) and the second factor was forage sowing rates (10, 12.5 and 15 kg ha-1), plus corn monoculture. For cowpea grown cultivation in succession, the straws from the intercropping were tested, allocated in the plots, and in the subplots the application or not of the herbicides imazamoxi + bentazon + fluazifop-p-butil in post-emergence. The intercropping system, regardless of U. ruziziensis sowing rates or glyphosate management, contributes to reducing weed infestation. The use of glyphosate reduced the production of U. ruziziensis straw at the time of corn harvest. However, the straw produced by the intercropping, regardless of treatments, did not contribute to the weeds control in the cowpea culture. The corn grain production and cowpea crops were not affected by the treatments tested.